Comprehensive Analysis of the Effects of Sacubitril/Valsartan According to Sex Among Patients With Heart Failure and Reduced Ejection Fraction in PARADIGM‐HF - Misato Chimura; Jawad H. Butt; Shingo Matsumoto; Eoghan G. M. McMurray; Alasdair D. Henderson; Atefeh Talebi; Akshay S. Desai; Martin P. Lefkowitz; Adel R. Rizkala; Jean L. Rouleau; Scott D. Solomon; Karl Swedberg; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Women with heart failure (HF) ejection fraction appeared to respond more favorably to sacubitril/valsartan, compared with valsartan, than men in PARAGON‐HF (Prospective Comparison of ARNI With ARB Global Outcomes in Heart Failure With Preserved Ejection Fraction), driven by a greater reduction in total (first and recurrent) HF hospitalizations. Sex‐specific efficacy and safety of sacubitril/valsartan in PARADIGM‐HF (Prospective Comparison of ARNI With ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure) remain unreported. Methods and Results This post hoc analysis of PARADIGM‐HF examined sex‐based outcomes in patients with HF and reduced ejection fraction randomized to sacubitril/valsartan or enalapril. The primary end point was a composite of cardiovascular death or HF hospitalization. Secondary and exploratory efficacy outcomes, biomarker changes, and safety outcomes were also assessed. Among 8399 participants, 1832 (21.8%) were women. Women were older, had worse New York Heart Association functional class and Kansas City Cardiomyopathy Questionnaire scores, more symptoms of HF, and lower estimated glomerular filtration rate, yet had lower rates of HF hospitalization (and other worsening of HF) and cardiovascular death than men. Compared with enalapril, sacubitril/valsartan reduced the risk of the primary end point to a similar extent in both sexes: hazard ratios, 0.76 (95% CI, 0.62–0.94) in women and 0.80 (95% CI, 0.73–0.89) in men (P‐interaction=0.62). Results were consistent for the individual components of the primary outcome. The rate ratio for total HF hospitalizations was 0.66 (95% CI, 0.48–0.89) in women and 0.80 (95% CI, 0.69–0.94) in men (P‐interaction=0.25). Randomized treatment discontinuation and adverse effects of interest were similar in women and men. Conclusions In PARADIGM‐HF, sacubitril/valsartan, compared with enalapril, reduced the risk of HF hospitalizations, death from cardiovascular causes, and death from any cause similarly in women and men with HF with reduced ejection fraction. In addition, sacubitril/valsartan was safe and well tolerated, irrespective of sex. Registration URL: https://www.clinicaltrials.gov; Unique Identifier: NCT01035255.